ORGANIZATION CULTURE MODERATES THE EFFECT OF MANAGEMENT ACCOUNTING SYSTEM, SUSTAINABLE LEADERSHIP AND ENVIRONMENTAL STRATEGY ON BUSINESS PERFORMANCE - Giawan Nur Fitria (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The purpose of this study was to determine whether there is an influence of management accounting system, sustainable leadership and environmental strategy on business performance with organizational culture as a moderating factor. The population in this study are 70 managers of manufacturing company in DKI Jakarta. Sampling technique using a convenience sampling method. Based on research result shows that the management accounting system does not affect business performance; sustainable leadership has a positive effect on business performance; the environmental strategy has a positive effect on business performance. Organization culture does not moderate influence of MAS, sustainable leadership and environmental strategy with business performance. The results showed that the management accounting system had no significant effect on business performance. This can be a special concern for company management in developing a management accounting information system. The availability of a management accounting information system can maximally assist company management in planning, monitoring and making decisions for business performance is better.